(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Bisera Alikadić is one of the key figures both in reconstructing women’s literary history in Bosnian literature as well as in speaking about contemporary literary producion. She cannot be subsumed under ethnonational categories (a Bosnian woman who writes erotic poetry and deals with topics nowhere suitable for the active process of building the nation). Her humour is subversive, emancipative, rebellious, and her position in the literary canon is permanently marginal. Poetically, her counterpart and colloqutor could be the Serbian female poet Radmila Lazić, and it is interesting to compare the poetics of these two autors who write in the same but differently named language – Serbian and Bosnian. Their lyrics demonstrate how humour works in love poetry, and what kind of love their poetry exhibits and affirms.